Phonemic Awareness as Predictor of Word Decoding Ability among Bachelor of Science in Information Technology Students - Genelza, Genesis (REiLA : Journal of Research and Innovation in Language, 2022)
This descriptive correlational study aimed at the level of Phonemic awareness as a predictor of Word Decoding ability among BS-IT students using a total enumeration technique that involves students enrolled in the course program. Moreover, it sought to determine the significant relationship between the two variables. To verify, three different tests were being utilised to collect the necessary data, i.e., a listening test for measuring the respondents' level of awareness of words with critical sounds; a phonetic transcription test to identify the respondents' level of awareness of sound-symbol relationship; and spelling test to know the respondents' level of ability for transcriptions to be translated to its American Standard English spelling. After the data had been collected and tabulated, it was interpreted that the students have a high level of Phonemic awareness with a mean of 3.66. Moreover, their Word Decoding ability resulted in a high level with a mean of 3.93. Further, it is being noticed that there is a tremendous significant relationship between the two variables with a p-value of 0.0000000859. With these findings, the researcher encourages the school, administrators, and teachers to give more exposure to sound-word connections by engaging the students with activities involving speaking, listening, reading, and writing activities and practice-based tasks.